Photoswitchable azobenzene-appended iridium(iii) complexes. Issue 35 (27th July 2016) - Pérez-Miqueo, J.; Altube, A.; García-Lecina, E.; Tron, A.; McClenaghan, N. D.; Freixa, Z.
Abstract : The use of aliphatic-bridging units to append azobenzene fragments on triscyclometalated Ir(iii ) complexes permits the construction of photoswitchable organometallics. Abstract : Iridium(iii ) cyclometalated complexes have been used as models to study the effect that extended conjugation and substitution pattern has on the photochromic behavior of azobenzene-appended 2-phenylpyridyl (ppy) ligands. For this purpose four azobenzene-containing ppy ligands were synthesized. With these ligands, nine iridium(iii ) complexes containing up to three appended azobenzenes were synthesized. Analysis of their photochromic behaviour by means of UV-vis and 1 H-NMR spectroscopy permitted us to conclude that the light-induced trans -to- cis isomerization of the azobenzene was strongly inhibited upon coordination to the Ir(iii ) cation when the electronic conjugation was extended along the whole ligand. The use of an aliphatic spacer unit (either –CH2 – or –OCH2 –) between the azobenzene and the ppy fragment of the ligand sufficed to disrupt the electronic communication, and obtain photochromic organometallic complexes.